PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS REALISTIC MATHEMATIC EDUCATIONS UNTUK SISWA KELAS V SEKOLAH DASAR - MARIA MAGDALENA ZAGOTO (Jurnal Education and Development, 2018)
This research goal is to produce a instructional material based realistic mathematics education are valid, practical and effective to increase the reanoning ability of student in the material fractions grade V elementary school. This research use Realistic Mathematics Education (RME) approach which principle; (1) guided reinvention and progressive mathematization, (2) didactical phenomenology, (3) self-developed models. RME has the characteristics that; (1) the use of context, (2) use models, bridging by vertical instrument, (3) student contribution, (4) interactivity, (5) intertwining. This research is a development research using Plomp model which phase: (1) preliminary research; (2) development or prototyping phase (3) assessment phase. Based on the result of the research conclude that RME-based instructional material developed was valid, practical and effective.